Methylbismuth: an organometallic bismuthinidene biradical. Issue 29 (15th June 2020) - Mukhopadhyay, Deb Pratim; Schleier, Domenik; Wirsing, Sara; Ramler, Jacqueline; Kaiser, Dustin; Reusch, Engelbert; Hemberger, Patrick; Preitschopf, Tobias; Krummenacher, Ivo; Engels, Bernd; Fischer, Ingo; Lichtenberg, Crispin
Abstract : Methylbismuth, the first organometallic non-stabilized bismuth(i ) compound, was generated in the gas phase and characterized. Implications for its chemistry in the condensed phase were investigated. Abstract : We report the generation, spectroscopic characterization, and computational analysis of the first free (non-stabilized) organometallic bismuthinidene, BiMe. The title compound was generated in situ from BiMe3 by controlled homolytic Bi–C bond cleavage in the gas phase. Its electronic structure was characterized by a combination of photoion mass-selected threshold photoelectron spectroscopy and DFT as well as multi-reference computations. A triplet ground state was identified and an ionization energy (IE) of 7.88 eV was experimentally determined. Methyl abstraction from BiMe3 to give [BiMe2 ] is a key step in the generation of BiMe. We reaveal a bond dissociation energy of 210 ± 7 kJ mol −1, which is substantially higher than the previously accepted value. Nevertheless, the homolytic cleavage of Me–BiMe2 bonds could be achieved at moderate temperatures (60–120 °C) in the condensed phase, suggesting that [BiMe2 ] and BiMe are accessible as reactive intermediates under these conditions.